FUNGSI TARI DUKUN PADA SUKU DAYAK BANYADU DI KECAMATAN TERIAK KABUPATEN BENGKAYANG - Apong, Apong; Fretisari, Imma; Ismunandar, Ismunandar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research to Â describe the function of Dukun dance Banyadu Dayak tribe, in Teriak sub-district. The problem of this research were how the function of Dukun dance Banyadu Dayak tribe, in Teriak sub-district. How to desaign the contribution of research results the function of Dukun dance Banyadu Dayak tribe, in Teriak sub-district. The method used in this research was descriptive method, with qualitative form and uses an anthropological approach. The source of data in this research was Sapon and Anel. The data in this research were, the results of interfiws and observations in the form of sound recordings, photographs and videos. the data collection techniques in this research were the form of observation, interview, and documentation techniques. Validity check of data in the form of extention of observation and triangulation. The data analysis techniques use interactive data analysis, wich is divided into four stages, including data collection, data reduction, data presentation, and power verification. The results of this research were expressive communication functions, ritual communication functions, ritual functions, and the results of this research were expected to be contribution in dance learning for cultural arts subjects and skills junior high school in the 2013 curiculum.Keywords: Dayak Banyadu in Bengkayang regency, The function of Dukun dance.